Dandy Walker Malformation Prenatal Diagnosis and Postnatal Outcome in Multigravida: A rare Case - Mustaqin, Mustaqin; Utami, Niken Asri; Dewi, Tgk. Puspa; Fandika, Bayu Azizka Putra (Journal of Society Medicine, 2025)
Introduction: Dandy Walker malformation (DWM) is a rare congenital anomaly characterized by cerebellar vermis hypoplasia, posterior fossa expansion, and fourth ventricle enlargement, often associated with hydrocephalus and chromosomal abnormalities like Trisomy 18 (Edwards syndrome). This case report describes the prenatal diagnosis and postnatal outcome of DWM in a multigravida patient. Case: A 43-year-old multigravida woman at 29–30 weeks’ gestation presented to Dr. Zainoel Abidin General Hospital with suspected fetal anomalies. Obstetric examination revealed a transverse fundal height of 23 cm, estimated fetal weight of 1,500 grams, fetal heart rate of 140 beats/min, and maternal hypertension (160/90 mmHg). Ultrasound identified DWM (absent cerebellar vermis, enlarged fourth ventricle), bilateral hydronephrosis, and undescended testes. The patient had a history of poorly controlled hypertension and reported owning a cat for one year but denied alcohol or smoking. Following counseling, pregnancy termination was performed, resulting in the delivery of a 1,400-gram male infant (length: 36 cm, Apgar score: 4–5). Postnatal phenotypic examination revealed undescended testes, low-set ears, overlapping digits, respiratory distress, small stature, and hypotonia. Karyotyping confirmed Trisomy 18. Conclusion: This case underscores the importance of prenatal ultrasound in detecting DWM and associated anomalies, enabling informed decision-making. The coexistence of DWM and Trisomy 18 highlights the need for genetic testing in such cases. Despite termination, the poor postnatal outcome reflects the severe prognosis of Trisomy 18. This report contributes to the limited literature on DWM in multigravida patients.